The Profile of Interferon-γ (IFN-γ) and Interleukin-10 (IL-10) in Pulmonary Tuberculosis Patients - Widya Wasityastuti; Yanri W Subronto; Marsetyawan HNE Soesatyo (Tropical Medicine Journal, 2011)
Introduction: Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis and becomes the main health problems in the world and in Indonesia, as well. The microorganism itself is an intracellular pathogen. The control of tuberculosis infection depends on cell-mediated immunity involving activated macrophages, T cells, and cytokines. The balance and dynamic changes between Th1 cytokine and Th2 cytokine refl ect the immune response of host and infl uence the clinical manifestation of the disease.Objectives: This research was designed to study the profi le and interaction of IFN-γ (Th1 cytokine) and IL-10 (Th2 cytokine) of pulmonary tuberculosis (PTB) patients in endemic area.Methods: Peripheral blood mononuclear cells of 23 pulmonary TB patients and 16 healthy persons was cultured and stimulated by phytohaemagglutinin (PHA) to investigate the ability to secrete IFN-γ and IL-10.Result: The result showed that there was a decreased of IFN-γ response to PHA in PTB patients, suggesting the defi ciency of general immune capacity in PTB. In contrast, IFN-γ secreted by specifi c antigen was higher in PTB patients which minimal lung lesion was higher than moderate-far advanced. It is related to IFN-γ roles as immunomodulator in cellular immunity and immunoprotectant through stimulated antimicrobial capacity in macrophage. In fact, IL-10 response to PHA and M.tuberculosis antigen in PTB patients was lower than that of in healthy persons; moderate-far advanced lung lesion was the lowest. It was probably refl ecting their poor general conditions. Paired distribution between IFN-γ and IL-10 pointed out the leaning of negative interaction. It refl ected the existence of counterpart/cross regulation between IFN-γ(Th1 cytokine) and IL-10 (Th2 cytokine).Conclusion: In conclusion that specifi c immune response of PTB is related to the degree of lung lesion. This study also provides the balance of Th1 cytokine and Th2 cytokine in relation to TB.Key words: tuberculosis, immune response, IFN-γ, IL-10, lung lesion